PENGARUH SUPERVISI AKADEMIK DAN MOTIVASI KERJA TERHADAP PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI SMP SWASTA PARULIAN 2 P. MANDALA MEDAN - Resmiwati Sinaga; Efendi Napitupupu; Sahala Siallagan (JURNAL PROINTEGRITA, 2021)
This study aims at analyzing the effect of academic supervision, the effect of work motivation and the effect of academic supervision and work motivation on increasing the pedagogical competence of teachers at SMP Parulian 2 P. Mandala Medan. The population used in this study are all 68 teachers and all of them are used as research samples. The data were collected using a questionnaire technique for the variables of academic supervision, work motivation and teacher pedagogical competence variables and documentation to obtain biographical data for the private SMP Swasta Parulian 2 P. Mandala Medan. Data were analyzed using product moment correlation and multiple correlation analysis. The results of the analysis show that there is an effect of academic supervision on teacher pedagogical competence with a coefficient of r = 0.611 or having moderate and positive strength. There is an effect of motivation on teacher pedagogic competence with a coefficient value of r = 0.694 or having moderate and positive strength. There is an effect of academic supervision and motivation on teacher pedagogical competence which is stated by the regression equation, namely Ŷ = 14.571 + 0.434 X1 + 0.737X2 with a contribution of 55.4%. The strength of the relationship is moderate and positive with a coefficient value of r = 0.744. Teachers can improve pedagogical competence through various activities, including teaching innovative learning techniques according to student character so that students understand the material presented more easily.